MEMBANGUN SISTEM INFORMASI KEPENDUDUKAN DESA TERUSAN OKU BERBASIS DESKTOP MENGGUNAKAN EMBARCADERO - Khafid, M. Shirotul; Wisnumurti, Wisnumurti; Trimarsiah, Yunita (JIK : Jurnal Informatika dan Komputer, 2024)
Terusan Village is a village in East Baturaja District, Ogan Komering Ulu Regency, South Sumatra Province. Terusan Village is the result of the expansion of the Sukajadi Village area in 2006, the Village Expansion is the result of the Deliberation of Education Leaders, Youth Leaders and Coral Taruna and BPD mothers in 2006. Sukajadi Village has expanded into two villages, namely Terusan Village and Sukajadi Village. The boundary is in the East of Tanjung Kemala Village in the West, Sukajadi Village in the North, Gotong Royong Village in the North of Batu Kuning Village. Each village is led by a village head and assisted by other village officials. The village area is divided into hamlets led by a Hamlet Head and given a sequence using numbers, such as hamlet one, hamlet two, and so on. Data collection is carried out by means of interviews, observations, and literature studies. The stages carried out in research are making database designs, user pages and data content display pages. Database created using Microsoft access, framework using embarcadero xe2. The result of the study is a population data information system located in the village of Terusan kec. East Baturaja kab. Oku. The page contains the data in Terusan Village including, population data, family card data, birth data, death data, immigrant data, and moving data, in Terusan Village. Keywords : Population Data, Terusan.